Setting priorities in the health care sector – the case of oral anticoagulants in nonvalvular atrial fibrillation in Denmark - Poulsen PB; Johnsen SP; Hansen ML; Brandes A; Husted S; Harboe L; Dybro L (Dove Medical Press, 2017)
Peter Bo Poulsen,1 Søren Paaske Johnsen,2 Morten Lock Hansen,3 Axel Brandes,4 Steen Husted,5,† Louise Harboe,6 Lars Dybro7 1Pfizer Denmark ApS, Ballerup, 2Department of Clinical Epidemiology, Aarhus University Hospital, 3Department of Cardiology, Zealand University Hospital, Roskilde, 4Department of Cardiology, Odense University Hospital, 5Department of Medicine, Regional Hospital West Jutland, Herning, 6Bristol-Myers Squibb Denmark, Virum, 7Pfizer Denmark, Ballerup, Denmark †Steen Husted passed away on December 28, 2016 Aim: Resources devoted to health care are limited, therefore setting priorities is required. It differs between countries whether decision-making concerning health care technologies focus on broad economic perspectives or whether focus is narrow on single budgets (“silo mentality”). The cost perspective as one part of the full health economic analysis is important for decision-making. With the case of oral anticoagulants in patients with nonvalvular atrial fibrillation (NVAF), the aim is to discuss the implication of the use of different cost perspectives for decision-making and priority setting. Methods: In a cost analysis, the annual average total costs of five oral anticoagulants (warfarin and non-vitamin K oral anticoagulants [NOACs; dabigatran, rivaroxaban, apixaban, and edoxaban]) used in daily clinical practice in Denmark for the prevention of stroke in NVAF patients are analyzed. This is done in pairwise comparisons between warfarin and each NOAC based on five potential cost perspectives, from a “drug cost only” perspective up to a “societal” perspective.Results: All comparisons of warfarin and NOACs show that the cost perspective based on all relevant costs, ie, total costs perspective, is essential for the choice of therapy. Focusing on the reimbursement costs of the drugs only, warfarin is the least costly option. However, with the aim of therapy to prevent strokes and limit bleedings, including the economic impact of this, all NOACs, except rivaroxaban, result in slightly lower health care costs compared with warfarin. The same picture was found applying the societal perspective.Conclusion: Many broad cost-effectiveness analyses of NOACs exist. However, in countries with budget focus in decision-making this information does not apply. The present study’s case of oral anticoagulants has shown that decision-making should be based on health care or societal cost perspectives for optimal use of limited resources. Otherwise, the risk is that suboptimal decisions will be likely. Keywords: atrial fibrillation, oral anticoagulants, priority setting, drug costs, total costs, silo thinking